2020
DOI: 10.1007/s11156-020-00908-7
|View full text |Cite
|
Sign up to set email alerts
|

Do more mergers and acquisitions create value for shareholders?

Abstract: How does an investor value the announcement of new business integration? The history of acquirer's acquisition may matter for investors. Existing research are divided to the positive or negative answer to the question. Based on the global evidence of 24,263 acquisitions across 81 countries over 19 years, this paper argues that the current contradictory views have failed to take into account the time interval between acquisitions. This is because the wavelength of merger frequency can change the investors' expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…The link between multiple acquisitions and overconfidence can also be traced to the notion that overconfidence increases the likelihood of succeeding in contests. More recently, Li et al ( 2021 ) analyse the difference in the time between M&A deals in 81 countries and document that multiple mergers undertaken in a short span of time generate lower abnormal returns. However, none of these extant studies have examined the effect of managers’ overconfidence on M&A in the post-financial crisis phase in the UK, which was characterised by significant regulatory overhaul, and this study addresses that gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The link between multiple acquisitions and overconfidence can also be traced to the notion that overconfidence increases the likelihood of succeeding in contests. More recently, Li et al ( 2021 ) analyse the difference in the time between M&A deals in 81 countries and document that multiple mergers undertaken in a short span of time generate lower abnormal returns. However, none of these extant studies have examined the effect of managers’ overconfidence on M&A in the post-financial crisis phase in the UK, which was characterised by significant regulatory overhaul, and this study addresses that gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that several financial measures failed to generate short-term operating benefits in the year before and after the merger event. An analysis of 24,263 M&A from 81 countries worldwide over 19 years found that the higher the number of M&A, the lower the abnormal returns [ 14 ]. Galariotis et al [ 15 ] evaluated the M&A performance of 43 listed commercial banks in 8 countries using data envelope analysis (DEA method) and found that M&A would have a negative impact on the efficiency level of “strong” and “weak” banking systems regardless of whether banks participated in one or more M&A.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%